2018
DOI: 10.3390/ani8110198
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Use on Goat Farms: An Investigation of Knowledge, Attitudes, and Behaviors of Missouri Goat Farmers

Abstract: Simple SummaryOveruse or inappropriate use of antibiotics in agriculture has been implicated in the development of antibiotic resistant bacteria, a significant and growing public health threat. In a previous study, we found that Missouri goats had a higher percentage of antibiotic residues at slaughter than predicted based on the national average, so we undertook this study to understand contributing factors. As farmers are typically the ones administering antibiotics to their animals, we set out to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Although there are many reasons that direct farmers to use antibiotics without consulting a veterinarian, self-diagnosis of diseases is a significant one. In a study on antibiotic use in goat farms conducted by Landfried et al, [15] the vast majority of farmers stated that they had sufficient knowledge about the behavior of animals and ability to identify abnormalities that might indicate a disease. The cost of veterinary services is one of the most important factors leading farmers to use antibiotics without consulting a veterinarian.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there are many reasons that direct farmers to use antibiotics without consulting a veterinarian, self-diagnosis of diseases is a significant one. In a study on antibiotic use in goat farms conducted by Landfried et al, [15] the vast majority of farmers stated that they had sufficient knowledge about the behavior of animals and ability to identify abnormalities that might indicate a disease. The cost of veterinary services is one of the most important factors leading farmers to use antibiotics without consulting a veterinarian.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, studies showed that healthcare workers were quite aware of the resistance problem [20,21,22]. However, it has been reported that farmers working in the livestock sector do not have sufficient awareness of the severity of the problems caused by antibiotic resistance [15,23]. In this study, the participants were firstly asked whether they had knowledge on antibiotic resistance before additional questions concerning antibiotic resistance and most of them responded negatively to this first question.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study performed in the United Kingdom, in 26 sheep farms, focusing on the potential associations between antibiotic administration and development of antimicrobial resistance, reported that farmers engaged in preventative measures, but they deflected responsibility for reducing antibiotic resistance to veterinarians [ 2 ]. In goat farms, Landfried et al [ 3 ] investigated the patterns of antibiotic use in 11 goat herds and found that in only four farms were antibiotics administered based on a veterinary prescription.…”
Section: Introductionmentioning
confidence: 99%
“…Antimicrobial therapy is used to treat mastitis in small ruminants along with antibiotic susceptibility testing to ensure optimum therapeutic action (Landfried et al, 2018). The emergence of multidrug-resistant bacteria has become a major threat to animal and human health (Parra et al, 2017).…”
Section: Introductionmentioning
confidence: 99%